Screening tests of tannins in overground organs of Zea mays L. - U. V. Karpiuk; V. S. Kislichenko; I. S. Cholak; O. I. Yemelianova (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
Aim. The introduction of new hemostatic drugs is a modern question. Using of tannins is promising especially for this segment of Pharmacy, as they are able to stop the bleeding. The purpose was to the study qualitative composition and quantitative content of tannins in Zea mays leaves and columns with stigmas.